The Effectiveness of the Strategic Planning of the Human Resources (The Educatinal System in the Sultanate of Oman as a Model) - Mohammed, M; Al-Yaaqoubi, ARS; Asma Abdul Rahman (Int Organization Center Acad Research, 2024)
Indexed by WOS